On the Verification of Adaptive Three-dimensional Multiresolution Computations of the Magnetohydrodynamic Equations - Gomes, Anna Karina Fontes; Domingues, Margarete Oliveira; Mendes, Odim; Schneider, Kai (Journal of Applied Nonlinear Dynamics, 2026)
Magnetohydrodynamics is an important tool to study the dynamics of Space Physics. In this context, we introduce a three-dimensional magnetohydrodynamic solver with divergence-cleaning in the adaptive multiresolution CARMEN code. The numerical scheme is based on a finite volume discretization that ensures the conservation of physical quantities. The adaptive multiresolution approach allows for automatic identification of local structures in the numerical solution and thus provides an adaptive mesh refined only in regions where the solution needs more improved resolution. We assess the threedimensional magnetohydrodynamic CARMEN code and compare its results with the ones from the well-known FLASH code.